Christian Metz and the codes of cinema : film semiology and beyond - Tröhler, Margrit; Kirsten, Guido, 1979- (Film theory in media history., 2018)
A pioneering figure in film studies, Christian Metz proposed countless new concepts for reflecting on cinema, rooted in his phenomenological structuralism. He also played a key role in establishing film studies as a scholarly discipline, making major contributions to its institutionalisation in universities worldwide. This book brings together a stellar roster of contributors to present a close analysis of Metz's writings, their theoretical and epistemological positions, and their ongoing influence today.